Enrichment of heavy metals from spent printed circuit boards by microwave pyrolysis. (15th May 2022) - Peng, Zhiwei; Wang, Jie; Zhang, Xin; Yan, Jiaxing; Shang, Wenxing; Yu, Jingfeng; Zhu, Guangyan; Rao, Mingjun; Li, Guanghui; Jiang, Tao
Graphical abstract: Highlights: Spent printed circuit boards (SPCB) had good microwave absorptivity. Reactions between heavy metals and hydrogen bromide were thermodynamically feasible. Metal discharge enhanced volatilizations of heavy metals in microwave pyrolysis. Metal enrichment was strongly affected by microwave power and pyrolysis temperature. Abstract: This study reports the enrichment behaviors of heavy metals, including copper, tin, lead and zinc, in the process of microwave pyrolysis of spent printed circuit boards (SPCBs). The SPCB had good microwave absorptivity. Under the optimal conditions of microwave power of 700 W, pyrolysis temperature of 400 °C, dwell time of 5 min, N2 gas flow rate of 1.2 L/min, and load mass of 5 g, the yield of pyrolyzed SPCB was 79.16%. The contents of copper, tin, lead, and zinc in the pyrolyzed SPCB were increased to 28.52 wt%, 7.15 wt%, 1.31 wt%, and 1.13 wt%, respectively, with the corresponding retention percentages of 99.98%, 85.89%, 92.59% and 82.06%. The loss of metals was attributed to volatilization of the elements, which was affected by metal discharge due to excitation of electrons in the metals under microwave irradiation. Little copper loss was found because of the difficult reaction between copper and hydrogen bromide and the very high temperature required by the volatilization of copper. Tin, lead and zinc were mainly volatilized in the form of their metal bromides, including SnBr4, ZnBr2, and PbBr2 . By controlling the pyrolysis conditions and metal discharge induced in the microwave field, the metals could be effectively enriched for subsequent treatment with high efficiency.